Nanoemulsion Therapy for Burn Wounds Is Effective as a Topical Antimicrobial Against Gram-Negative and Gram-Positive Bacteria. Issue 2 (March 2016) - Dolgachev, Vladislav A.; Ciotti, Susan M.; Eisma, Rone; Gracon, Stephen; Wilkinson, J. Erby; Baker, James R.; Hemmila, Mark R.
Abstract : The aim of this study is to investigate the antimicrobial efficacy of two different nanoemulsion (NE) formulations against Gram-positive and Gram-negative bacteria in an in vivo rodent scald burn model. Male Sprague-Dawley rats were anesthetized and received a partial-thickness scald burn. Eight hours after burn injury, the wound was inoculated with 1 × 10 8 colony-forming units of Pseudomonas aeruginosa or Staphylococcus aureus. Treatment groups consisted of two different NE formulations (NB-201 and NB-402), NE vehicle, or saline. Topical application of the treatment was performed at 16 and 24 hours after burn injury. Animals were killed 32 hours after burn injury, and skin samples were obtained for quantitative wound culture and determination of dermal inflammation markers. In a separate set of experiments, burn wound progression was measured histologically after 72 hours of treatment. Both NE formulations (NB-201 and NB-402) significantly reduced burn wound infections with either P. aeruginosa or S. aureus and decreased median bacterial counts at least three logs when compared with animals with saline applications ( p < .0001). NB-201 and NB-402 also decreased dermal neutrophil recruitment and sequestration into the wound as measured by myeloperoxidase (MPO) assay and histopathology ( p < .05). In addition, there was a decrease in the proinflammatory dermal cytokines (interleukin 1-beta [IL-1β], IL-6, and tumor necrosis factor alpha [TNF-α]) and the neutrophil chemoattractants CXCL1 and CXCL2. Using histologic examination, it was found that both NB-201 and NB-402 appeared to suppress burn wound progression 72 hours after injury. Topically applied NB-201 and NB-402 are effective in decreasing Gram-positive and Gram-negative bacteria growth in burn wounds, reducing inflammation, and abrogating burn wound progression.